Out of Mind, Out of Sight: A Critical Appraisal of Social Initiatives to Curb Migration in Uttarakhand - Amanjeet Singh Sethi, (International Journal of Management, Technology and Social Sciences (IJMTS), 2019)
The existing state of affairs in the hill and rural areas of Uttarakhand is very dangerous as the state has more than fifteen hundred ghost villages and this number is growing day in day out. The villagers from these places are moving out to plain areas within and outside the state mainly for employment opportunities and a variety of other reasons also contributes to this unfortunate process. Comprehending the urgency of the situation several individuals, non-government organizations, self help groups and the different agencies of the government have started a number of initiatives to curb this serious issue of migration. This research article makes an effort to study the circumstances, current scenario and predominant causes in relation to migration for the state of Uttarakhand. The research article mainly focusses on some of the successful cases of social initiatives attempted for helping to create a viable environment so that people do not have to migrate out of their home in search for facilities. The article concludes that such kind of social initiatives have the potential to stop the process of migration and to initiate reverse migration in the state but still a fair distance has to be covered to make this vision palpable.